2018
DOI: 10.1136/bmjgast-2018-000203
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies in chronic hepatitis C virus infection: impact on clinical outcomes and extrahepatic manifestations

Abstract: GoalsTo examine the role that autoantibodies (auto-abs) play in chronic hepatitis C virus (HCV) regarding demographics, presence of extrahepatic manifestations and long-term outcomes in a large US cohort.BackgroundAuto-abs have been reported to be prevalent in patients with chronic HCV infection, but data on the natural history of these patients are limited.StudyThe study included 1556 consecutive patients with HCV without concurrent HIV and/or HBV who had testing for antinuclear antibody (ANA), antimitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
7
21
1
Order By: Relevance
“…In contrast to our study, however, they only tested patients with acute hepatitis E, and not with chronic or asymptomatic HEV infection. In line with our data, Gilman et al reported a rate of ANA positivity of 22% in a cohort of 1556 chronic HCV patients [35], whereas, in the German general population, the rate of ANA positivity was reported to be 33% (defined as a titer ≥1:80) [38].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast to our study, however, they only tested patients with acute hepatitis E, and not with chronic or asymptomatic HEV infection. In line with our data, Gilman et al reported a rate of ANA positivity of 22% in a cohort of 1556 chronic HCV patients [35], whereas, in the German general population, the rate of ANA positivity was reported to be 33% (defined as a titer ≥1:80) [38].…”
Section: Discussionsupporting
confidence: 91%
“…In line with these data, the presence of autoantibodies has also been associated with HEV infection. This was very much like other forms of viral hepatitis [13,30,33,35,36]. However, it has not yet been clarified whether cryoglobulins or autoantibodies have a pathogenetic impact and contribute to overt disease in HEV-infected individuals.…”
Section: Introductionmentioning
confidence: 85%
“…Infections would play a central role in triggering autoimmunity and autoantibody production in patients with PIDs. In fact, the presence of autoantibodies such as ANA, RF, ACPA, aPL, ANCA and ASMA has been described as an epiphenomenon in several bacterial and viral infections (ex., Staphylococcus aureus , Mycobacterium tuberculosis and HCV ) ( 30 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that HCV could induce transient autoimmune responses leading to development of autoantibodies classically associated with AIH, and it has been reported that chronic HCV infections that were autoantibody positive were more common in women, exhibited more severe transaminase elevation, and had histologic evidence of liver injury . A study by Gilman et al also showed that autoantibody positivity in HCV infection was more common in women; their presence predicted a lower rate of achieving SVR when using IFN‐based regimens, but their presence did not otherwise affect the natural history of chronic HCV or presence of extrahepatic manifestations. In the current study, the majority of patients who were HCV+ that had serum markers of AIH were female patients (12/21, 57.1%), and liver biopsies from these patients showed significantly more inflammatory activity and slightly increased fibrosis compared to controls.…”
Section: Discussionmentioning
confidence: 99%